2008
DOI: 10.1007/s12325-008-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockers in the treatment of NASH/NAFLD: Could they be a first-class option?

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a condition pathogenically linked to metabolic syndrome (MS) by insulin resistance (IR), and characterized by hepatic steatosis in the absence of significant alcohol use, hepatotoxicity, and/or other known liver diseases.The principles of NAFLD therapy target IR: the key point of MS. As the renin-angiotensin system (RAS) plays a central role in IR, and subsequently in NAFLD and nonalcoholic steatohepatitis (NASH), an attempt to block the deleterious effects of RAS ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 190 publications
(291 reference statements)
0
47
1
10
Order By: Relevance
“…Of course, a reasonable explanation could be the specific PPARγ modulatory activity of this ARB, but also other unique properties of this drug can contribute to this effect. As extensively discussed elsewhere [15] , it seems that various ARBs have different "second-level" pharmacologic effects, unrelated to presence or absence of certain PPAR-modulating activity, as for example candesartan, which shows capacities to decrease liver fibrosis and diminish portal pressure in Child A cirrhotic patients [65] , but do not have significant PPAR-modulating activity. It is subsequently possible that the better clinical results observed for telmisartan are driven through some undisclosed mechanism(s) that further studies will undoubtedly unveil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, a reasonable explanation could be the specific PPARγ modulatory activity of this ARB, but also other unique properties of this drug can contribute to this effect. As extensively discussed elsewhere [15] , it seems that various ARBs have different "second-level" pharmacologic effects, unrelated to presence or absence of certain PPAR-modulating activity, as for example candesartan, which shows capacities to decrease liver fibrosis and diminish portal pressure in Child A cirrhotic patients [65] , but do not have significant PPAR-modulating activity. It is subsequently possible that the better clinical results observed for telmisartan are driven through some undisclosed mechanism(s) that further studies will undoubtedly unveil.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no major studies have been performed to confirm its efficacy in steatohepatitis, although a theoretical and experimental fundament exists [15] . Interestingly, a study by Fujita et al [16] tested the same compounds as we did in this study in a rat model of NASH, providing evidence that telmisartan, but not valsartan, improved both qualitatively and quantitatively hepatic steatosis, inflammation, and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II may contribute to the pathogenesis of hyperglycemia in NAFLD patients via its regulative effects on adiponectin. ACEIs and ARBs used to be considered potential treatments for NAFLD (31). However, clinical evidence regarding the efficiency of ACEIs and ARBs in NAFLD patients is limited to those with hypertension or T2D.…”
Section: Discussionmentioning
confidence: 99%
“…106 Previous studies showed that the renin-angiotensin system may be up-regulated during liver injury contributing to recruitment of inflammatory cells and activation of stellate cells, and that the use of angiotensin-receptor inhibitors attenuated these effects and improved liver enzymes and histology. [107][108][109] Attempts to block RAS overexpression with the use of angiotensin-converting enzyme inhibitors (ACEI) or angiotensin-II receptor blockers (ARBs) thus could be beneficial for patients with NAFLD and NASH.…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin-ii mentioning
confidence: 99%